Religious and Cultural Diversity: The Chinese Village Community of Padang City - Irwan, Irwan; Syakia, Gina; Hidayah, Windy Anastasya Nur; Siska, Felia; Sulkaisi, Neffi (PT Inovasi Pratama Internasional, 2024)
Kampung Cina is known as an area with cultural and religious diversity in carrying out daily life activities. This diversity certainly has differences in life. The purpose of this research is to analyze the diversity of religion and culture in the community in Kampung Cina in Padang City. Theoretical analysis uses pluralism theory or interculturalism theory. Pluralism theory highlights the existence of diverse beliefs and values in society that coexist harmoniously, while interculturalism theory emphasizes the importance of intercultural interaction and exchange to create better understanding among different groups. This research uses a qualitative approach with a descriptive research type. Data collection methods were carried out in three stages, namely participant observation, in-depth interviews and document studies. Data analysis used the Milles and Huberman analysis model. The results of this study indicate that the people of Kampung Cina Padang City live side by side and do not cause conflict. The attitude of tolerance between religions and cultures is very strong and creates a harmonious life. In addition, people live in harmony with each other and have an attitude of mutual respect and appreciation